Epistemics & economics : a critique of economic doctrines - Shackle, G. L. S. (Cambridge, England : University Press, 1972)
It is Shackle's view that human conduct is chosen with a view to its consequences. But these are in the future, which cannot be directly known. Expectation will confine itself to what is deemed possible, but this leaves it free to entertain widely diverse and rival hypotheses. How can such skeins of mutually conflicting ideas serve the formation of individual or institutional policy? This is the chief question this book examines.
Includes bibliographical references and index.
rpm 10/07/2017
Loans
Keywords: Epistemics; Economics; Economic Theory; Political Economy; Economic History